2008
DOI: 10.1021/pr700742h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Therapy for Breast Carcinoma by ATP Synthase Inhibitor Aurovertin B

Abstract: Targeting of tumor tissues is one of the most powerful approaches to accelerate the efficiency of anticancer treatments. The investigation of effective targets, including proteins specifically and abundantly expressed in abnormal regions, has been one of the most important research topics in cancer therapy. In this study, we performed a proteomic analysis on human breast carcinoma tissues to investigate the tumor-specific protein expression in breast carcinoma. Our study showed that ATP synthase was up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
109
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 48 publications
7
109
0
Order By: Relevance
“…Our study revealed that citreoviridin treatment resulted in significant changes of phosphorylation levels in numerous proteins. Furthermore, we observed that the cell cycle, protein folding, and mRNA processing might be regulated by citreoviridin-stimulated responses, consistent with previous reports (10,18,66). We also identified other processes that have not been reported to be related to citreoviridin treatment, such as cytoskeletonassociated function, development regulation, and ubiquitinproteasomal proteolysis.…”
Section: Discussionsupporting
confidence: 92%
“…Our study revealed that citreoviridin treatment resulted in significant changes of phosphorylation levels in numerous proteins. Furthermore, we observed that the cell cycle, protein folding, and mRNA processing might be regulated by citreoviridin-stimulated responses, consistent with previous reports (10,18,66). We also identified other processes that have not been reported to be related to citreoviridin treatment, such as cytoskeletonassociated function, development regulation, and ubiquitinproteasomal proteolysis.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, ectopic ATP synthase may be an antigen of tumor cells and involved in the immune response to tumor cells. Treating these cancer cells with biological (i.e., antibody or inhibitor of F 1 of ATP synthase, IF1) or chemical synthetic inhibitors of ectopic ATP synthase markedly inhibits cell growth (15,17), thereby highlighting ectopic ATP synthase as a potential and novel therapeutic target for cancer.…”
Section: Unlike In Normal Cells Its Function In Tumor Cellsmentioning
confidence: 99%
“…Although ectopic ATP synthase has been found on the extracellular surface of several different cancer cell types (6,(14)(15)(16)…”
Section: Introductionmentioning
confidence: 99%
“…This protein can even play an important role as a target protein in the treatment of cancers. Using ATP synthase inhibitor aurovertin B, in breast cancer cells MCF-7, the effect of ATP5B protein in tumor progression was found to be reduced (Huang et al, 2008).…”
Section: Prognosismentioning
confidence: 99%